2007
DOI: 10.1128/iai.01254-06
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensis Replicates within Alveolar Type II Epithelial Cells In Vitro and In Vivo following Inhalation

Abstract: Francisella tularensis replicates in macrophages and dendritic cells, but interactions with other cell types have not been well described. F. tularensis LVS invaded and replicated within alveolar epithelial cell lines. Following intranasal inoculation of C57BL/6 mice, Francisella localized to the alveolus and replicated within alveolar type II epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 19 publications
5
130
0
Order By: Relevance
“…This approach is a well established technique for exploring inflammasome activity (12, 13). 293T cells, like type II lung epithelial cells (42), can be infected with Francisella and support intracellular replication (Fig. 3A).…”
Section: Response Of Thp-1 Cells To Infection With Francisella-tlrmentioning
confidence: 99%
“…This approach is a well established technique for exploring inflammasome activity (12, 13). 293T cells, like type II lung epithelial cells (42), can be infected with Francisella and support intracellular replication (Fig. 3A).…”
Section: Response Of Thp-1 Cells To Infection With Francisella-tlrmentioning
confidence: 99%
“…Because IL-17Rs are expressed on a wide variety of cell types, including leukocytes and epithelial cells, and many of these cell types can support the growth of Francisella species (13,32,33), we investigated the direct impact of IL-17A on control of LVS growth in host cells. Interestingly, we found that IL-17A can cooperate with IFN-g to inhibit growth of LVS in alveolar epithelial cells and macrophages.…”
Section: Cd8mentioning
confidence: 99%
“…The in vitro culture and LVS infection of TC-1 cells has been previously described (13). One day prior to infection, RAWand TC-1 cells were plated at 2 3 10 5 viable cells per well in 24-well plates in cDMEM.…”
Section: Animals Infections and Determination Of Bacterial Organ Bumentioning
confidence: 99%
“…Francisella infects primarily monocytes and macrophages [2], and has the ability to escape from the host cell phagosome and replicate in the cytoplasm. The subspecies F. novicida is commonly used as an infection model because it is non-virulent in normal humans yet leads to fatal tularemia in mouse models [3].…”
Section: Introductionmentioning
confidence: 99%